Digital Teaching Schedule Development Through Community Engagement at SMAN 24 - Rio Guntur Utomo; Parman Sukarno; Isa Mulia Insan (MATRADIPTI, 2025)
The development of a teaching scheduling system at SMAN 24 Bandung aims to enhance the efficiency and effectiveness of time management and educational resource allocation. SMAN 24 Bandung has faced challenges with manual scheduling, which often leads to schedule conflicts, misalignment with curriculum requirements, and suboptimal use of resources. This technology-based scheduling system is designed to automate the scheduling process, reduce the potential for errors, and allow for real-time schedule adjustments. The proposed solution includes the development of a flexible system, training for users (teachers and administrative staff), phased implementation, and continuous monitoring and evaluation. Intensive training and user empowerment ensure optimal system utilization, while ongoing monitoring and evaluation are conducted to assess effectiveness and make adjustments as needed. With this development, SMAN 24 Bandung is expected to create a more structured, efficient, and adaptive learning environment, thereby contributing to improved educational quality and student academic achievement.